Quasi-classical trajectory study of the OH− + CH3I reaction: theory meets experiment. Issue 5 (17th January 2023) - Tasi, Domonkos A.; Michaelsen, Tim; Wester, Roland; Czakó, Gábor
Abstract : Dynamics of the OH − + CH3 I reaction is studied using a high-level ab initio analytical potential energy surface and the quasi-classical trajectory method allowing direct comparison with crossed-beam experiments. Abstract : Regarding OH − + CH3 I, several studies have focused on the dynamics of the reaction. Here, high-level quasi-classical trajectory simulations are carried out at four different collision energies on our recently developed potential energy surface. In all, more than half a million trajectories are performed, and for the first time, the detailed quasi-classical trajectory results are compared with the reanalysed crossed-beam ion imaging experiments. Concerning the previously reported direct dynamics study of OH − + CH3 I, a better agreement can be obtained between the revised experiment and our novel theoretical results. Furthermore, in the present work, the benchmark geometries, frequencies and relative energies of the stationary points are also determined for the OH − + CH3 I proton-abstraction channel along with the earlier characterized SN 2 channel.